1963
DOI: 10.1017/s0022029900011249
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the properties of new zealand butterfat: VI. Comparison of the properties and vitamin A potencies of butterfats produced by clover-fed and ryegrass-fed dairy cows

Abstract: In an indoor feeding trial with three sets of monozygotic twin cows during late spring the effects of H x short rotation ryegrass and white clover as feeds for the cows on the characteristics and the carotene and vitamin A contents of the butterfat were compared. The butterfat from the cows fed ryegrass had a lower iodine value and refractive index, higher Reichert and saponification values, and lower carotene and vitamin A contents than the butterfat from the cows fed clover. The carotene and vitamin A conten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1963
1963
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…In a previous experiment (McDowall 1963) in which the production was measured from cows fed white clover and Manawa ryegrass, the clover-fed cows produced a lower yield of milk. The combined results suggested that mixed pasture was superior to the pure ryegrasses in the present experiment because of an interaction of c!over with ryegrass, rather than a gross superiority of clover over ryegrass.…”
Section: Discussionmentioning
confidence: 93%
“…In a previous experiment (McDowall 1963) in which the production was measured from cows fed white clover and Manawa ryegrass, the clover-fed cows produced a lower yield of milk. The combined results suggested that mixed pasture was superior to the pure ryegrasses in the present experiment because of an interaction of c!over with ryegrass, rather than a gross superiority of clover over ryegrass.…”
Section: Discussionmentioning
confidence: 93%
“…A lactational effect on the level of C 18 fatty acids, consisting of a rapid fall early in lactation followed by a more steady decline, was reported by Decaen & Adda (1966). Workers in New Zealand, however, have shown that seasonal changes in iodine value and other characteristics of milk fat are related to the stage of maturity of the ryegrass in the pastures (McDowall, 1962;McDowall, McGillivray & Hawke, 1961;McDowall & McGillivray, 1963a, b), while Hawke (1963 showed that the fatty-acid composition of milk fat from cows grazed on immature ryegrass was more unsaturated than that from cows grazed on mature ryegrass. These findings would indicate that, in New Zealand, pasture lipids have a greater influence on C 18 acids than do lactational effects.…”
Section: Discussionmentioning
confidence: 99%
“…The previous findings were expected because the summer milk fat contained higher levels of C 4 and C 6 acids than the one found in the winter milk fat (Laurelle et al 1976). However, this discrepancy between both fats and in their fatty acid levels was due to the effect of the season of the year and consequently the plane of nutrition (McDowall and McGillivary, 1963;Hall, 1970;Gray, 1973). The BR reading was found to be lower (P<0.05) in summer compared to winter season.…”
Section: Effect Of Season On Milk Yield Milk Composition and Physicochemical Parameters Of Gheementioning
confidence: 90%